2002
DOI: 10.1046/j.1365-2958.2002.02807.x
|View full text |Cite
|
Sign up to set email alerts
|

A distinctive single‐stranded DNA‐binding protein from the Archaeon Sulfolobus solfataricus

Abstract: Summary Single‐stranded DNA binding proteins (SSBs) have been identified in all three domains of life. Here, we report the identification of a novel crenarchaeal SSB protein that is distinctly different from its euryar‐chaeal counterparts. Rather than comprising four DNA‐binding domains and a zinc‐finger motif within a single polypeptide of 645 amino acids, as for Methanococcus jannaschii, the Sulfolobus solfataricus SSB protein (SsoSSB) has a single DNA‐binding domain in a polypeptide of just 148 amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
64
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 56 publications
2
64
1
Order By: Relevance
“…In contrast, members of the archaea harbor different forms of singlestranded DNA (ssDNA) binding proteins that are more similar to their eukaryotic counterpart at the amino acid sequence level (9,(11)(12)(13)(14). The archaeal RPA proteins are either single polypeptides (9,11,12,25) or heterocomplexes of more than one protein (5,14).In the mesophilic archaeon Methanosarcina acetivorans we demonstrated the presence of three functional RPA proteins (22), which are also conserved in its relatives Methanosarcina mazei and Methanosarcina barkeri. Two of the RPA proteins were of similar architecture, in that both proteins (M. acetivorans RPA2 [MacRPA2] and MacRPA3) have two OB folds within the N-terminal half and a zinc finger domain in the C-terminal half (22).…”
mentioning
confidence: 91%
“…In contrast, members of the archaea harbor different forms of singlestranded DNA (ssDNA) binding proteins that are more similar to their eukaryotic counterpart at the amino acid sequence level (9,(11)(12)(13)(14). The archaeal RPA proteins are either single polypeptides (9,11,12,25) or heterocomplexes of more than one protein (5,14).In the mesophilic archaeon Methanosarcina acetivorans we demonstrated the presence of three functional RPA proteins (22), which are also conserved in its relatives Methanosarcina mazei and Methanosarcina barkeri. Two of the RPA proteins were of similar architecture, in that both proteins (M. acetivorans RPA2 [MacRPA2] and MacRPA3) have two OB folds within the N-terminal half and a zinc finger domain in the C-terminal half (22).…”
mentioning
confidence: 91%
“…Although many hypothetical RPA proteins have been identified in the numerous genomes analyzed, there is no quaternary structure that is common to all. In the crenarchaea, the RPA from Sulfolobus solfataricus is encoded by a single gene and exists as a monomer or a homotetramer (Haseltine & Kowalczykowski, 2002;Kerr, et al, 2001;Kerr, et al, 2003;Wadsworth & White, 2001). The different quaternary structures confer distinct binding capabilities (Rolfsmeier & Haseltine, 2010).…”
Section: Multiplicity Of Homologsmentioning
confidence: 99%
“…The different quaternary structures confer distinct binding capabilities (Rolfsmeier & Haseltine, 2010). Despite the similarity to bacterial SSB, and the ability of the gene to complement the lethality of an E. coli ssb mutation, the DNA-binding domain of this protein more closely resembles those of eukaryotic RPA1 (Haseltine & Kowalczykowski, 2002;Kerr, et al, 2003). Although the genomes of two related crenarchaea, P. aerophilum and A. pernix, have been reported to contain no obvious RPA or SSB homolog (Luo, et al, 2007), a previous study found a Sulfolobus-like SSB in A. pernix (Haseltine & Kowalczykowski, 2002).…”
Section: Multiplicity Of Homologsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SsoRPA contains a single OB fold, and while it has been reported to oligomerize to form a homotetramer (6), a different report found that the protein exists as monomers (23). In the Euryarchaeota, RPAs display an unusual diversity and distribution.…”
mentioning
confidence: 99%